The Impact of Corporate Governance Mechanisms on Organization Performance: Evidence from The UK Charities - LIU, Qiang (2020)
In recent years, the role of charitable organizations in the world has become increasingly prominent, but compared with the research of listed companies, research in this field is seriously insufficient. This article explores the relationship between charity governance mechanisms and organizational performances by using a sample of the top 50 UK charities by income. The fixed effects regression model shows that the size of the board and the frequency of board meetings have a positive impact on organizational performance. However, distinct other studies, audit committees and diversity damage the performance of the organizations. Finally, this article do not find a significant relationship between the independence of the board of directors and the ROA of the organizations. Therefore, this article proposes to appropriately expand the size of the board of directors and the number of meetings to improve the performances of charities in order to promote the realization of organizational goals.